Match Bias in Wage Gap Estimates Due to Earnings Imputation - Hirsch, Barry T.; Schumacher, Edward J. (Journal of Labor Economics, 2004)
About 30% of workers in the Current Population Survey have earnings imputed. Wage gap estimates are biased toward zero when the attribute being studied (e.g., union status) is not a criterion used to match donors to nonrespondents. An expression for “match bias” is derived in which attenuation equals the sum of match error rates. Attenuation can be approximated by the proportion with imputed earnings. Union wage gap estimates with match bias removed are presented for 1973–2001. Estimates for recent years are biased downward 5 percentage points. Bias in gap estimates accompanying other non–match criteria (public sector, industry, etc.) is examined.